2021
DOI: 10.3389/fnagi.2021.648115
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Suppressed Hypoxia-Inducible Factor-1 Transactivation of Angiogenesis With Defective Recovery From Cerebral Ischemic Injury in Aged Rats

Abstract: Elderly patients suffer more brain damage in comparison with young patients from the same ischemic stroke. The present study was undertaken to test the hypothesis that suppressed hypoxia-inducible factor-1 (HIF-1) transcription activity is responsible for defective recovery after ischemic stroke in the elders. Aged and young rats underwent 1-h transient middle cerebral artery occlusion (MCAO) to produce cerebral ischemic injury. The initial cerebral infarct volume in the young gradually declined as time elapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Many factors are related to neurological deficits following ICH, including primary brain injury, edema, inflammation, and age (Keep et al, 2012;Guo et al, 2021). In this study, GLC improved neurological deficits, consistent with previous studies (Liew et al, 2012;Xu et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Many factors are related to neurological deficits following ICH, including primary brain injury, edema, inflammation, and age (Keep et al, 2012;Guo et al, 2021). In this study, GLC improved neurological deficits, consistent with previous studies (Liew et al, 2012;Xu et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we employed a rat model of MCAO and revealed that young rats exhibited a better ability to resist cerebral ischemic injury than adult rats. Many previous experimental studies have shown that the degree of stroke-induced ischemic injury depends on the ability of the brain to recover from these injuries and that this ability decreases with age [ 20 ]. Thus, there is a close relationship between age-dependent brain self-recovery and the ability of young animals to reduce cerebral focal IR injury [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the complement system genes, including C1QA, C1QB, C1QC, C1S, C3, C3AR1, C4α, C4β, C5, and C5AR1, are significantly upregulated with age ( Cribbs et al, 2012 ). Additionally, with age, angiogenesis and neurogenesis that may contribute to recovery are diminished, as pro-angiogenic genes ANGPT2 and VEGFA are significantly downregulated ( Guo et al, 2021 ). Genes related to synaptic transmission, axonal projection, dendrite growth, and neuroplasticity show age-related downregulation ( Blalock et al, 2003 ; Lu et al, 2004 ; Verbitsky et al, 2004 ; Burger et al, 2007 ; Aenlle and Foster, 2010 ; Zeier et al, 2011 ; Berchtold et al, 2019 ; Androvic et al, 2020 ).…”
Section: “Inflammaging”mentioning
confidence: 99%